LAYOUT DESIGN AND DREDGING PROJECT OF NAVIGATION CHANNEL AND TUNING BASIN AT DRY BULK TERMINAL IN THE C PIER OF DUMAI PORT - E M Sirait, Maria
Dumai Port is one of the main ports in Indonesia. It serves as a distribution route for various commodities, including dry bulk cargo, which is loaded and unloaded at Berth C. In the year 2029, the total dry bulk cargo handling at Berth C is expected to reach 4 million tons. The largest dry bulk vessel that will dock there is a 90,000 DWT ship with a draft of 14.65 meters. However, the current navigational channel depth and turning basin around Berth C are not sufficient for accommodating such a vessel's draft. Therefore, dredging works are required to deepen the water bottom. Based on the design, the dredged depth of the navigational channel and turning basin will be 16.5 meters from LWS, the channel width will be 270 meters, the turning basin diameter will be 495 meters, and the seabed slope will be at an angle of 35°. Using the cross-section method, the total dredged volume is estimated to be 2,387,414.357 m^3. The dredging operations will be carried out using one unit of TSHD "Inai Petunia," with a total project duration of 92 days, including mobilization and demobilization. The estimated cost for this dredging project is approximately Rp123,632,833,831 or around Rp44,000/????3.